Theory of the free-carrier absorption in quantum wires with boundary roughness scattering - Ibragimov, G.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A theory of free carrier absorption is given for quantum wires when carriers are scattered by boundary roughness and the radiation field is polarized along the length of the wire. The free-carrier absorption coefficient is found to be an oscillatory function of the photon frequency and of the wire width. The obtained results are compared with different scattering mechanisms for quasi-one-dimensional structures. It is found that boundary roughness scattering is important especially when the wire width and temperature decreases. In addition, it was found that in quantum wire the electron - boundary roughness interaction gives a greater contribution to the absorption than the electron-acoustic phonon interaction. The results are interpreted in terms of boundary roughness-assisted transitions between size quantized subbands.